Question
upstudy study bank question image url

Solve for \( w \). \( 4+\frac{3}{w-3}=-\frac{5}{w-4} \) If there is more than one solution, separate them with commas. If there is no solution, click on "No solution".

Ask by Wood Clarke. in the United States
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solutions are \( w = \frac{3}{2} \) and \( w = \frac{7}{2} \).

Solution

Solve the equation \( 4+\frac{3}{w-3}=-\frac{5}{w-4} \). Solve the equation by following steps: - step0: Solve for \(w\): \(4+\frac{3}{w-3}=-\frac{5}{w-4}\) - step1: Find the domain: \(4+\frac{3}{w-3}=-\frac{5}{w-4},w \in \left(-\infty,3\right)\cup \left(3,4\right)\cup \left(4,+\infty\right)\) - step2: Multiply both sides of the equation by LCD: \(\left(4+\frac{3}{w-3}\right)\left(w-3\right)\left(w-4\right)=-\frac{5}{w-4}\times \left(w-3\right)\left(w-4\right)\) - step3: Simplify the equation: \(4w^{2}-25w+36=-5w+15\) - step4: Move the expression to the left side: \(4w^{2}-25w+36-\left(-5w+15\right)=0\) - step5: Calculate: \(4w^{2}-20w+21=0\) - step6: Factor the expression: \(\left(2w-7\right)\left(2w-3\right)=0\) - step7: Separate into possible cases: \(\begin{align}&2w-7=0\\&2w-3=0\end{align}\) - step8: Solve the equation: \(\begin{align}&w=\frac{7}{2}\\&w=\frac{3}{2}\end{align}\) - step9: Check if the solution is in the defined range: \(\begin{align}&w=\frac{7}{2}\\&w=\frac{3}{2}\end{align},w \in \left(-\infty,3\right)\cup \left(3,4\right)\cup \left(4,+\infty\right)\) - step10: Find the intersection: \(\begin{align}&w=\frac{7}{2}\\&w=\frac{3}{2}\end{align}\) - step11: Rewrite: \(w_{1}=\frac{3}{2},w_{2}=\frac{7}{2}\) The solutions to the equation \(4+\frac{3}{w-3}=-\frac{5}{w-4}\) are \(w = \frac{3}{2}\) and \(w = \frac{7}{2}\).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equation \( 4 + \frac{3}{w - 3} = -\frac{5}{w - 4} \), we start by isolating the fractions. 1. Subtract 4 from both sides: \(\frac{3}{w - 3} = -\frac{5}{w - 4} - 4\). 2. To combine the terms on the right side, convert 4 into a fraction: \(-4 = -\frac{4(w - 4)}{w - 4} = -\frac{4w - 16}{w - 4}\). 3. Now we have: \(\frac{3}{w - 3} = -\frac{5 + 4w - 16}{w - 4} = -\frac{4w - 11}{w - 4}\). 4. Cross-multiply: \(3(w - 4) = - (4w - 11)(w - 3)\). 5. Expanding both sides: \(3w - 12 = -(4w^2 - 12w + 33)\). 6. Rearranging terms gives: \(4w^2 - 12w + 33 + 3w - 12 = 0\), which simplifies to \(4w^2 - 9w + 21 = 0\). 7. Attempting to factor or use the quadratic formula: \(w = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{9 \pm \sqrt{(-9)^2 - 4(4)(21)}}{2(4)}\). 8. The discriminant is \((-9)^2 - 4(4)(21) = 81 - 336 = -255\). Since the discriminant is negative, the equation has no real solutions. The final answer is: No solution.

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy